Law and the visible - Sarat, Austin; Douglas, Lawrence; Umphrey, Martha Merrill (Amherst : University of Massachusetts Press, 2021)
"If you take a video of police officers beating a Black man into unconsciousness, are you a witness or a bystander? If you livestream your friends dragging the body of an unconscious woman and talking about their plans to violate her, are you an accomplice? Do bodycams and video doorbells tell the truth? Are the ubiquitous technologies of visibility open to interpretation and manipulation? These are just a few of the questions explored in the rich and broadly interdisciplinary essays within this volume, Law and the Visible, the most recent offering in the Amherst Series for Law, Jurisprudence, and Social Thought. Individual essays discuss the culpability of those who record violence, the history of racialized violence as it streams through police bodycams, the idea of digital images as objective or neutral, the logics of surveillance and transparency, and a defense of anonymity in the digital age. Contributors include Benjamin J. Goold, Torin Monahan, Kelli Moore, Eden Osucha, Jennifer Peterson, and Carrie A. Rentschler"--
Ubiquitous video, objectivity, and the problem of perspective in digital visual evidence / Jennifer Petersen -- The pessimistic eye using automatic reporting devices in studies of perceptual bias in legal reasoning / Kelli Moore -- Mediating responsibility visualizing bystander participation in sexual violence / Carrie A. Rentschler -- Between the body-cam and the black body the post-panoptic racial interface / Eden Osucha -- Visualizing the surveillance archive critical art and the dangers of transparency / Torin Monahan -- Becoming invisible privacy and the value of anonymity / Benjamin J. Goold.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on September 02, 2021).
JSTOR
Keywords: Electronic evidence -- United States; Digital video -- United States; Wearable video devices in police work -- United States; Video recordings -- Law and legislation -- United States; Audio-visual materials -- Law and legislation -- United States; Preuve électronique -- États-Unis.; Vidéo numérique -- États-Unis.; Caméras corporelles dans le travail de la police -- États-Unis.; LAW / General; Wearable video devices in police work; Video recordings -- Law and legislation; Electronic evidence; Digital video; Audio-visual materials -- Law and legislation; United States